An Eye on Vision: Five Questions About Vision Screening and Eye Health—Part 3. (September 2018) - Nottingham Chaplin, P. Kay; Baldonado, Kira; Cotter, Susan; Moore, Bruce; Bradford, Geoffrey E.
Current evidence-based and best practice vision screening and eye health approaches, tools, and procedures are the result of revised national guidelines in the past 3 years and advances in research during the past 18 years. To help the busy school nurse with little time to keep up with changes in children's vision practices and a growing body of literature, the National Center for Children's Vision and Eye Health at Prevent Blindness is providing answers to five questions that are often received from the field. Topical areas are: (1) instrument-based screening for children ages 6 years and older, (2) stereoacuity screening and Random Dot E, (3) binocular distance visual acuity screening, (4) a 2-line difference between the eyes as part of referral criteria, and (5) state vision screening guidelines excluding evidence-based tools.